2024
DOI: 10.1308/rcsann.2023.0065
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Heller’s cardiomyotomy for achalasia: early outcomes for a high-volume UK centre

EJ Nevins,
K Greene,
S Bawa
et al.

Abstract: Introduction Heller’s cardiomyotomy (HCM) is the gold standard treatment for achalasia. Laparoscopic HCM has been shown to be effective with low rates of symptom recurrence, though oesophageal mucosal perforation rates remain high. The aim of this prospective case series is to assess the short-term complication rates and perioperative outcomes for the first cohort of patients undergoing robotic-assisted HCM for achalasia in a single high-volume UK centre. Methods Data were collected from a prospective cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[14] Early cases series on robotic Heller myotomies report excellent post-operative symptom relief, noninferior to that of the established laparoscopic approach with acceptable intraoperative and postoperative complication rate. [15][16][17][18][19][20][21][22][23] In fact, Kim et al presented superior average length of myotomy and improved symptom control with the robotic approach, while Raja et al demonstrated superior long-term symptom relief and decreased reintervention rate when comparing robotic to laparoscopic myotomy. [16,23] A number of studies report reduced incidence of intraoperative complication rate, mainly mucosal tears while using the robotic platform [15,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…[14] Early cases series on robotic Heller myotomies report excellent post-operative symptom relief, noninferior to that of the established laparoscopic approach with acceptable intraoperative and postoperative complication rate. [15][16][17][18][19][20][21][22][23] In fact, Kim et al presented superior average length of myotomy and improved symptom control with the robotic approach, while Raja et al demonstrated superior long-term symptom relief and decreased reintervention rate when comparing robotic to laparoscopic myotomy. [16,23] A number of studies report reduced incidence of intraoperative complication rate, mainly mucosal tears while using the robotic platform [15,18,20,22].…”
Section: Discussionmentioning
confidence: 99%